PENGARUH INOVASI PRODUK LOKAL TERHADAP PERMINTAAN MASYARAKAT DAN PERTUMBUHAN PEREKONOMIAN - Wulandari, Shalsa; Afriyana, Maya; Syamab, Ridho Vinandhito; Panorama, Maya (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2025)
Innovative local products have become essential for generating community demand and promoting long-term economic growth. The purpose of this research is to analyze the Influence of Local Product Innovation on Community Demand and Economic Growth. The research method employed is a literature review obtained from previous journals. Innovative locally produced products are increasingly crucial in meeting consumer needs amid intense global competition and rapidly changing market dynamics. This study analyzes how innovation can provide a competitive advantage, add value, and enhance the quality of locally produced goods. Local products can offer relevant, effective, and sustainable solutions through the right innovation, making them a preferred choice for environmentally-conscious consumers who prioritize quality. Innovative local products enable market expansion and the opportunity to generate income from outside the region. This encourages sustainable economic growth and creates new employment opportunities. Keywoards: Product  Inovation, Community Demand, Economic Growth